2012
DOI: 10.1029/2012gl053449
|View full text |Cite
|
Sign up to set email alerts
|

Is cumulus convection the concertmaster of tropical cyclone activity in the Atlantic?

Abstract: [1] The influence of the cloud representation in global climate models on the accuracy of the North Atlantic tropical cyclone simulations is investigated. The North Atlantic tropical cyclone activity is simulated with a standard climate model, CCSM. The conventional parameterization of cloud processes in CCSM is replaced by the "super-parameterization" and the simulation is run again. The comparison of tropical cyclone statistics reveals that the model with explicit representation of cloud processes produces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…3) show features similar to those obtained for 2005 in the sense that the increased thresholds of minimum entrainment produce larger number of TCs with longer life cycles and a track variety more similar to the observation over the Atlantic. This model response is consistent with Emanuel et al (2008) and Stan (2012), who showed a sensitivity of TC activity to changes in the cumulus parameterization in the Community Climate System Model (CCSM; Gent et al 2011 Noda et al (2012) and Putman and Suarez (2011) has been shown to be beneficial for explicitly simulating convection and capturing such extremely strong hurricanes. Mallard et al (2013) explored the resolution dependence of TC simulations by comparing runs with 6-km and 18-km grid spacing, using the Weather Research and Forecasting Model (WRF).…”
Section: Sensitivity Of Tc Characteristics To Changes In Parameterizesupporting
confidence: 64%
See 2 more Smart Citations
“…3) show features similar to those obtained for 2005 in the sense that the increased thresholds of minimum entrainment produce larger number of TCs with longer life cycles and a track variety more similar to the observation over the Atlantic. This model response is consistent with Emanuel et al (2008) and Stan (2012), who showed a sensitivity of TC activity to changes in the cumulus parameterization in the Community Climate System Model (CCSM; Gent et al 2011 Noda et al (2012) and Putman and Suarez (2011) has been shown to be beneficial for explicitly simulating convection and capturing such extremely strong hurricanes. Mallard et al (2013) explored the resolution dependence of TC simulations by comparing runs with 6-km and 18-km grid spacing, using the Weather Research and Forecasting Model (WRF).…”
Section: Sensitivity Of Tc Characteristics To Changes In Parameterizesupporting
confidence: 64%
“…Knutson and Tuleya (2004), LaRow et al (2008), Ma and Tan (2009), and Reed and Jablonowski (2011) performed model experiments to examine the sensitivity of the global TC numbers to changes in the convective parameterizations. Shen et al (2006) and Stan (2012) examined the impact of disabling the convective parameterizations [in particular the schemes developed by Arakawa and Schubert (1974) and Moorthi and Suarez (1992)] on GCM hurricane forecasts. Both studies agreed on that explicit representation of cloud processes produces a larger number of TC events, with stronger intensity and longer life cycles (Reed and Jablonowski 2011;Stan 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong wind, heavy rainfall and storm surge are the ways through which TC inflicts the damage on striking the coast in the preferred locations of the earth and impact the human society by destabilizing the socio-economic conditions and GDP of the nations (WMO 2010;Probst and Franchello 2012). The coupled ocean-atmospheric phenomenon, largescale atmospheric circulation, and cloud-scale processes associated with enhanced cumulus convection play a crucial role on the onset and development of the TC over the tropical ocean waters (Stan 2012). Apart from the pre-existing low level cyclonic disturbances as a pre-cursor, climatological conditions such as warm sea surface temperatures (SST's) above 26.5°C with a deep oceanic mixed layer, a conditionally unstable atmosphere, weak vertical wind shear, high relative vorticity, mid-troposphere high relative humidity and presence of moist convection provide the conducive environment for TC formation (Gray 1975;Frank 1977;Liang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the pre-existing low level cyclonic disturbances as a pre-cursor, climatological conditions such as warm sea surface temperatures (SST's) above 26.5°C with a deep oceanic mixed layer, a conditionally unstable atmosphere, weak vertical wind shear, high relative vorticity, mid-troposphere high relative humidity and presence of moist convection provide the conducive environment for TC formation (Gray 1975;Frank 1977;Liang et al 2014). Stan (2012) has argued that a region of organized convective activity is also necessary for the TC activity to occur. Also he indicated that the mesoscale organization of cumulus convection acts as a thermodynamic engine of the TC's.…”
Section: Introductionmentioning
confidence: 99%